The measure of the contribution of multiculturalism in constructing the current Brazilian Constitutional text - E. R. Hogemann (Law and Safety)
Recognizing the importance of diversity through multiculturalism and its relationship with improvement of democracy through intercultural dialogues has been proposed. It has been considered the notion of multiculturalism and its acceptance with consequent and reaffirmation of human rights, as well as challenges inherent to realization of human rights in multicultural environment established by 1988 constitutional text. It is appropriate to mention the works of Parekh, Santos, and Taylor. With the help of the legal-descriptive method, through bibliographic review, legislative documents and analysis of examples, the relevance of the contribution of the theory of multiculturalism to the affirmation of human rights and the guarantee of a democratic legal state has been demonstrated.